Pengaruh Kepemimpinan Transformasional dan Kepercayaan Interpersonal Terhadap Organizational Citizenship Behavior Karyawan [Effect Of Transformational Leadership and Interpersonal Trust on Employee's Organizational Citizenship Behavior] - Ie, Mei; Widjaja, Oey Hannes (Feedforward: Journal of Human Resource, 2021)
One of the factors that encourage organizational citizenship behavior is transformational leadership. Transformational leadership encourages organizational citizenship behavior that is voluntary and is not directly connected to the organizational reward system, but contributes to improving organizational effectiveness and climate. Apart from transformational leadership, a factor that can affect organizational citizenship behavior is interpersonal trust. When the interpersonal trust among employees is very strong, they tend to show strong Organizational Citizenship Behavior. The purpose of this study was to determine the effect of transformational leadership and interpersonal beliefs on organizational citizenship behavior. Researchers distributed questionnaires to 100 respondents. The sampling method is probability sampling with a simple random sampling type. The data analysis method in this study is a quantitative method and Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results of this study state that transformational leadership affects organizational citizenship behavior and interpersonal beliefs affect organizational citizenship behavior of employees.BAHASA INDONESIA ABSTRACT:Salah satu faktor yang mendorong terjadinya organizational citizenship behavior adalah kepemimpinan transformasional. Kepemimpinan transformasional mendorong organizational citizenship behavior yang bersifat sukarela dan tidak terhubung langsung ke sistem penghargaan organisasi, tetapi berkontribusi untuk meningkatkan efektivitas dan iklim organisasi. Selain kepemimpinan transformasional, faktor yang dapat mempengaruhi organizational citizenship behavior adalah kepercayaan interpersonal. Ketika kepercayaan interpersonal di antara karyawan sangat kuat, mereka cenderung menunjukkan perilaku Organizational Citizenship Behavior yang kuat. Tujuan penelitian ini adalah untuk mengetahui pengaruh dari kepemimpinan transformasional dan kepercayaan interpersonal terhadap organizational citizenship behavior. Peneliti menyebarkan kuesioner kepada 100 responden. Metode pengambilan sampel adalah probability sampling dengan jenis simple random sampling Metode analisis data dalam penelitian ini adalah metode kuantitatif dan Structural Equation Modelling (SEM) dengan pendekatan Partial Least Squares (PLS). Hasil dari penelitian ini menyatakan bahwa kepemimpinan transformasional berpengaruh terhadap organizational citizenship behavior dan kepercayaan interpersonal berpengaruh terhadap organizational citizenship behavior karyawan.